Synthesis and Characterization of a Trisheteroleptic Ru-II-Based Molecular Switch - Monczak, Katharina; Peuntinger, Katrin; Sorsche, Dieter; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Rau, Sven (Chemistry - A European Journal, 2014)
The synthesis of a trisheteroleptic ruthenium complex [Ru(tb)(dppz)(tmbiH(2))][PF6](2) (tb = 4,4'-di-tert-butyl-2,2'-bipyridine, dppz = dipyrido[3,2-a:2',3'-c]phenazin, tmbiH(2) = 5,6,5',6'-tetramethyl-2,2'-bibenzimidazole) is described. In addition, the structural characterisation by means of 1D, 2D H-1 NMR spectroscopy, and mass spectrometry, along with determination of the solid-state structure of the important precursor Ru(tb)(dppz) Cl-2, supports the proposed octahedral coordination geometry. The capability of tmbiH(2) to form hydrogen bonds is corroborated by the solid-state structure. The photochemical characteristics of this complex can be described as a combination of the "light switch" effects, which are either attributed to the dppz or to the tmbiH(2) ligand. To illustrate the molecule's double switchable features, steady-state absorption and emission measurements were performed, which include the determination of the quantum yield and the pK(a) values of the acidic protons of the tmbiH(2) ligand. Notably, the emission lifetimes are sensitive to the solvents used. This phenomenon is due to a proton-coupled deactivation of the excited metal-to-ligand charge transfer (MLCT) state of the complex.
Keywords: bibenzimidazole; light switch effect; molecular switch; pH dependency; trisheteroleptic Ru-II complex